Upaya GoPay Terhadap Mahasiswa di Kantin UNTAR Kampus 1 - Livia Gracely Wahyu; Eko Harry Susanto; Sisca Aulia (Prologia, 2020)
As time goes by, Technology and the economy creates new innovations that help human life, which is called financial technology (fintech). Financial Technology has a function to accelerate and facilitate various access to human finance. One of the companies in Indonesia that applies financial technology is GoJek. GoJek created GoPay as a financial technology that can be used to pay for all services in the GoJek application. However, now GoPay has developed and can be used in tenants who have collaborated with GoPay, such as Tarumanagara University Canteen Campus 1, which since 2019 has been working with GoPay so that students can transact using GoPay as a payment tool. Therefore, the researcher discusses GoPay's efforts in maintaining student purchase interest at Tarumanagara University. This research methodology is qualitative with a case study method based on the results of data from key informants / informants who have influence in this study. Based on the results of the interview, GoPay gave some efforts to students in the Tarumanagara University Campus 1 canteen.Teknologi dan ekonomi yang berkembang seiring berkembangnya zaman menciptakan inovasi baru yang menolong hidup manusia, yang disebut dengan financial technology (fintech). Financial Technology memiliki fungsi untuk mempercepat dan mempermudah berbagai akses keuangan manusia. Salah satu perusahaan di Indonesia yang mengaplikasikan financial technology adalah GoJek.  GoJek menciptakan GoPay sebagai financial technology yang dapat digunakan untuk membayar semua layanan di aplikasi GoJek. Namun, sekarang GoPay sudah berkembang dan dapat digunakan di tenant-tenant yang sudah bekerja sama dengan GoPay, seperti Kantin Universitas Tarumanagara Kampus 1 yang sejak tahun 2019 sudah bekerja sama dengan GoPay sehingga mahasiswa dapat bertransaksi menggunakan GoPay sebagai alat pembayarannya. Oleh sebab itu, peneliti membahas mengenai upaya GoPay dalam mempertahankan minat pembelian mahasiswa di Universitas Tarumanagara. Metodologi penelitian ini adalah kualitatif dengan metode studi kasus berdasarkan hasil data dari narasumber/ key informan yang memiliki pengaruh dalam penelitian ini. Berdasarkan hasil wawancara, GoPay memberikan beberapa upaya terhadap mahasiswa di kantin Universitas Tarumanagara Kampus 1.